Peran Orientasi Kewirausahaan Sebagai Mediasi Antara Pendidikan dan Minat Berwirausaha Pada Mahasiswa - Devi, Abrista (Li Falah: Journal of Islamic Economics and Business, 2017)
Nowadays, university is focused on how to prepare their graduated student to be anemployee, but forgetting on how to prepare them to be an entrepreneur. There are someobstacles why university students have lack of an intention to do business, starting with lackof capital, lack of skill, have no confidence, selective in choosing job, and some other factors.These problems is strengthtened by the data found that Indonesia is highly need moreentrepreneurs, where the numbers of entrepreneurs is still less than 2% from total GDP(Gross Domestic Product of a country). This study is aimed to identify the effect ofentrepreneurial education to entrepreneurial orientation of university student, the effect ofentrepreneurial orientation to entrepreneurial intention, and the direct and indirect effect ofentrepreneurial education to entrepreneurial intention. This study takes Ibn KhaldunUniversity, Islamic Economics major students as case study of respondents. This studyemploys quantitative approach with SEM (Structural Equation Modeling) methodology.The findings of this study are, entrepreneurial education has positive and significant effect toentrepreneurial orientation; entrepreneurial orientation has positive and significant effect toentrepreneurial intention; and entrepreneurial education has positive and significant effect toentrepreneurial intention indirectly through entrepreneurial orientation.